Does judicial review influence the quality of Local Authority Services? - Kerman Calvo; Lucinda Platt; Maurice Sunkin (University of Essex, Institute for Social and Economic Research (ISER), 2007)
This paper raises some of the key issues that have emerged from our study of the impact of judicial review litigation on the quality of local government services in England and Wales. Judicial Review is the High Court procedure by which those with a sufficient interest can challenge decisions of public authorities on the grounds that authorities have failed to meet their legal obligations, including human rights obligations; or have acted unfairly or exceeded or abused their legal powers (or threatened to do these things). The paper discusses whether or not a greater engagement with public law litigation, as experienced in the UK in recent times, may be leading to improvements or declines in access to services and in service delivery for individuals and classes of services user, to improvements in the clarity and accountability of processes within local authorities, and to greater levels of legal awareness, including the furtherance of the practical application of the rule of law. We focus on two areas of local authority activity: housing and homelessness and childrens services; and we distinguish in the paper between the impact of challenges, and the impact of judicial decisions. The paper draws on a series of qualitative interviews with key informants in local authorities; and presents analyses of judicial review decisions of national significance in the area of childrens services. Our conclusions at this stage are tentative and indicate areas that we intend to pursue further. Our most general observation is that judicial review is a significant aspect of an environment that over the past two decades has subjected local authorities to an increasing range of external regulatory and controlling mechanisms. Against this background, we observe that judicial review is distinctive in various ways. We identify several potentially distinctive features of judicial review from a quality perspective, including its focus on individual problems, its ability to subject decisions to close scrutiny and its ability to provide authoritative statements as to local authorities duties. We also consider the circumstances under which decisions are likely to have most (or least) impact on the working and quality of local authority services.
Keywords: 330